Fate and future of the medical students in Ukraine: A silently bubbling educational crisis - Jain, Nityanand; Panag, Deepkanwar Singh; Srivastava, Mahek; Mohan, Srinithi; Chodnekar, Swarali Yatin; Akbari, Amir Reza; Raj, Divyam; Kravarioti, Dionysia; Świątek, Dorota; Platos, Emilia; Khetsuriani, Ketevani; Gristina, Kitija Lucija; et al. (Medical education, 2022)
Jain et al. reflect on the Russia‐Ukraine war and argue that although there is a broad consensus on the need for intervention, focus should be on providing immediate accommodative measures.
Keywords: Education, Medical; Educational Status; Ukrajina; studenti lékařství; lidé; stupeň vzdělání; studium lékařství; Students, Medical; Ukraine; Humans